IMPLEMENTASI MODEL PROBLEM BASED LEARNING BERDIFERENSIASI (PAPAN JODOH) UNTUK MENINGKATKAN PEMAHAMAN SISWA - Rahmawati, Diana Anisa; Reni Untarti; Sri Rahayu Puji Astuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Low conceptual understanding, minimal active student involvement, and a lack of differentiation in Science and Social Studies (IPAS) learning in elementary schools are major problems. This study aims to implement a differentiated Problem-Based Learning (PBL) model using Pondoh media to improve the conceptual understanding of fifth-grade students at SD Negeri 2 Purwokerto Lor. Using the Classroom Action Research (PTK) approach based on the spiral model by Kemmis and McTaggart, this study was conducted in three cycles encompassing planning, action, observation, and reflection. The research subjects were 22 fifth-grade students, with data collected through formative tests, observations, documentation, and interviews, then analyzed qualitatively and quantitatively. The research results showed a significant improvement in conceptual understanding. In Cycle I, achievement reached 68.18% with an average score of 66.82, increased to 90.91% with an average score of 83.64 in Cycle II, and achieved 100% achievement in Cycle III with an average score of 88.18. The ability to interpret, classify, and connect concepts showed consistent development. The differentiated PBL approach using Pondoh media proved effective in enhancing active engagement and holistic understanding among students, aligning with the diversity of learning characteristics. This approach is recommended for widespread implementation in thematic learning under the Merdeka Curriculum in elementary schools.